Allergen-Specific Immunotherapy in Children: Prospects of Prevention and Treatment - E. A. Vishnyova; L. S. Namazova-Baranova (Union of pediatricians of Russia, 2015)
Global spread of allergic diseases due to both environmental degradation, uncontrolled drug use and dietary changes, appearance of new allergens is a severe burden for the healthcare budget not only of the developing, but also of the advanced countries. Devastating symptoms considerably reduce quality of life both of patients and of their family members; allergy is one of the most significant medical/social issues. The contemporary understanding is that a complex approach is required to achieve control over allergic diseases; at the same time, the only pathogenetic method of treating and preventing new allergy manifestations is allergenspecific immunotherapy. The accumulated experience of using this technology indicates clinical/economic advantages of the method; moreover, on-going studies have proved not only therapeutic, but also preventive action of ASIT.